2018
DOI: 10.1016/j.theriogenology.2017.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Quality evaluation of sperm from livebearing fishes: Standardized assessment of sperm bundles (spermatozeugmata) from Xenotoca eiseni (Goodeidae)

Abstract: Standardized evaluation of sperm quality is essential for research, commercial-scale cryopreservation, and induced spawning. However, standardized methods for evaluation of sperm bundles (spermatozeugmata or spermatophores) have not been established. The purpose of the present study was to use Redtail Splitfin (Xenotoca eiseni) as a model for freshwater livebearing fishes to establish initial standardized methods to collect sperm bundles, and quantitatively and qualitatively evaluate quality-related attributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…Livebearing fishes from the family Poeciliidae and Goodeidae each produce sperm bundles, however the independent evolution of the viviparity for these two groups resulted in different reproductive characteristics. For example, milt can be collected by stripping from poeciliids but not from goodeids [23]. As such, males were euthanized in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Livebearing fishes from the family Poeciliidae and Goodeidae each produce sperm bundles, however the independent evolution of the viviparity for these two groups resulted in different reproductive characteristics. For example, milt can be collected by stripping from poeciliids but not from goodeids [23]. As such, males were euthanized in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed sperm from X. eiseni could not be collected by stripping [23]. As such, fish were euthanized by exposure to 300 mg/l Tricaine methanesulfonate (MS-222, Western Chemical, Inc. WA, USA) followed by severing of the spinal column behind the head.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The viviparous goodeids discharge semen in large aggregates of cysts filled with spermatozoa, called spermatozeugmata, into the deferent ducts (spermiation) whereas empetrichthyins release “free sperm.” The presence of spermatozeugmata in goodeins has been documented previously (Grier et al, ; Uribe et al, , ). In species of the subfamily Goodeinae, as in Ilyodon whitei (see Grier et al, ; Grier and Uribe, ), Xenotoca eiseni (see Grier and Uribe, ; Liu, Torres, & Tiersch, , ; Uribe et al, ), Goodea atripinnis (see Liu et al, ; Uribe et al, ) and Ataeniobius toweri (see Liu et al, ), large groups of cysts with spermatozoa are bundled in spermatozeugmata in the testis and in the deferent ducts. The spermatozeugmata are formed by an enveloping layer of mucotic substance secreted by the Sertoli cells (Fishelson, Gon, Holdengreber, & Delarea, ).…”
Section: Discussionmentioning
confidence: 99%
“…Each of a total of 5–15 spermatozeugmata distributed across the viewing area were categorized into one of five phases by evaluating morphology of the spermatozeugmata and motion of sperm within the spermatozeugmata as Phase 0 (P 0 ) through Phase 4 (P 4 ), representing early through later dissociation stages. The frequencies of each dissociation phase (FDP) were referred as FDP 0 through FDP 4 and were used to evaluate dissociation of spermatozeugmata and motility capability of sperm within the spermatozeugmata (Liu et al, 2017). At P 0 , the spermatozeugmata were quiescent; At P 1 , sperm were activated within spermatozeugmata but remained associated; At P 2 , the spermatozeugmata dissociated and sperm within them swam away; At P 3 , sperm stopped swimming away from the spermatozeugmata but remained vibrating in place; At P 4 , all sperm movement ceased.…”
Section: Methodsmentioning
confidence: 99%